A Study on the Optimization Mechanism of the Civic OBE Concept for a Computational Thinking-Oriented Basic Programming Course - Xiong, Hao; Talha, Muhammad (Mathematical problems in engineering, 2022)
This paper conducts an in-depth study and analysis of the optimization mechanism of the Civic OBE concept through the basic programming course of computational thinking. The connotation, implementation principles, and key points of the OBE concept are thoroughly studied and analyzed, and the new requirements of knowledge, ability, and quality of applied talents are specifically analyzed with the characteristics of applied talents in local undergraduate institutions and demand-oriented; the “top-down” idea is fully considered, and the top-down design is based on the middle school IT learning objectives. The reverse design focuses on the cultivation of skills and emotional goals, satisfies students’ individual needs, and enhances students’ ability to analyze and solve problems, and, second, to adapt to the rapid information society, the development of online open platforms, the use of information technology, the integration of modern learning resources, changing the traditional classroom teaching, and stimulating students’ learning enthusiasm and autonomy, to truly achieve efficient classroom. Based on this, this study tries to provide some new ideas and contribute some strengths to the design and practice research of information technology education in junior high school. In the process of effect analysis, data analysis was conducted on the achievement of the competency index points and related achievements of the research subjects. Oral interviews were also conducted with the teachers and students who participated in the experiment to explore the effectiveness of the project-based learning teaching model based on the OBE concept and to summarize the shortcomings of the model in teaching.